Mechanism and Anticancer Activity of the Metabolites of an Endophytic Fungi from Eucommia ulmoides Oliv - Li, Qi; Zhang, Yan; Shi, Jun-Ling; Wang, Yi-Lin; Zhao, Hao-Bin; Shao, Dong-yan; Huang, Qing-Sheng; Yang, Hui; Jin, Ming-Liang (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Backgroud: Pinoresinol (Pin) and pinoresinol monoglucoside (PMG) are plant-derived lignan molecules with multiple functions. We showed previously that an endophytic fungus from Eucommia ulmoides Oliv., Phomopsis sp. XP-8 is able to produce Pin and PMG. Objective: This study was carried out to test the anti-tumor capability of the culture of XP-8 and identify the major effective compounds. Method: The fungal culture was added in the culture of HepG2 and K562 cells, and the viabilities of these cells were detected and the possible mechanism was analyzed. Result: The fungal culture showed significant capaiblity in decreasing the viability of tumor cells and induce apoptosis via up-regulation of the expression of apoptosis-related genes. It also significantly inhibited the adhesion and migration of HepG2 cells by blocking MMP-9 expression. Pin and PMG were isolated from the growth culture and shown to be the major effective components for inhibition. Conclusion: The study indicated the potential application of XP-8 in the production of anti-tumour products by the bioconversion of glucose.
Keywords: pinoresinol